Factors That Affect PERCIST-Defined Test-Retest Comparability: An Exploration of Feasibility in Routine Clinical Practice. (December 2015) - Yuan, Hui; Tong, Daniel King Hung; Vardhanabhuti, Varut; Khong, Pek-Lan
Abstract : Purpose: The aim of this study was to evaluate the factors affecting the comparability of 18 F-FDG PET/CT scans using the PERSIST criteria for treatment response evaluation in a clinical PET/CT unit. Patients and Methods: Patients diagnosed with esophageal cancer were assessed for treatment response by comparing 2 18 F-FDG PET/CT scans, at baseline (PET 1) and 1 month after the end of induction chemoradiation (PET 2). According to the PERCIST recommendations, patients with mean SUV normalized by the lean body mass within reference volume of interest that changed less than 0.3 unit and less than 20% were deemed as comparable. Absolute differences of body weight, blood glucose level, activity of 18 F-FDG, and uptake time between the 2 scans were computed. Binary logistic regression was used to identify the predictive factors, and receiver operating characteristic curves were used for thresholds. P < 0.05 was considered statistically significant. Results: Sixty-nine subjects were identified. The mean (SD) values at PET 0 and PET 2 were 5.9 (1.04) mmol/L and 6.2 (1.06) mmol/L ( P = 0.013), 54.6 (10.0 kg) and 53.3 (10.3 kg) ( P = 0.013), 7.7 (1.3 mCi) and 7.6 (1.5 mCi) ( P = 0.349), as well as 74.2 (12.4) minutes and 73.0 (12.3) minutes ( P = 0.539), for blood glucose level, body weight, injected activity, and uptake time, respectively. Seventeen (24.6%) failed to match the PERCIST-defined comparability criteria. Case-based discrepancies (mean [SD]) were 0.76 (0.62) mmol/L, 3.4 (2.9) kg, 0.8 (0.7) mCi, and 11.7 (9.8) minutes for blood glucose, body weight, injected activity, and uptake time, respectively, of which only uptake time significantly affected comparability ( P = 0.046; odds ratio, 1.06; 95% confidence interval, 1.00–1.12), with a limit of 2.2-minute discrepancy identified as the requirement for 100% comparability. Conclusions: Uptake time had the strongest effect on PERCIST-defined comparability. Therefore, for response assessment scans, reference to initial scans for determination of optimal uptake time is recommended.